Severe renal impairment as an adverse prognostic factor for survival in newly diagnosed multiple myeloma patients. Issue 9 (25th July 2020) - Chen, Xuduan; Luo, Xiaofeng; Zu, Yanping; Issa, Hajji Ally; Li, Linlin; Ye, Hong; Yang, Ting; Hu, Jianda; Wei, Lixin
Abstract: Background: Renal impairment (RI) is associated with poor survival in newly diagnosed multiple myeloma (MM) patients. Renal function recovery has been one of the main therapeutic goals in those patients. Methods: The records from 393 newly diagnosed MM patients in our hospital between January 2012 and December 2016 were retrospectively analyzed. RI was defined as an eGFR < 40 mL/min according to the novel IMWG criteria. RI patients were categorized based on their renal function at diagnosis: severe RI: eGFR < 30 mL/min, and mild RI: 30 mL/min ≤ eGFR <40 mL/min. We explored whether RI, and particularly severe RI, was an adverse prognostic factor for survival, and investigated the impact of renal function recovery on survival. Results: Severe RI, hemoglobin <100 g/L, LDH ≥ 245 U/L, hyperuricemia, 1q21 amplification, and lack of novel agent treatment were associated with decreased overall survival (OS). Severe RI patients with renal response had a median OS of 27 months compared with 18 months for those patients without renal response ( P  = .030), but their median OS was still significantly lower than that for patients without severe RI, which was 51 months. In severe RI patients, the overall renal response rate in bortezomib‐based regimens was significantly higher than that in nonbortezomib‐based regimens. Conclusion: Our results suggest that severe RI is an adverse prognostic factor for survival in newly diagnosed MM patients, restoration of renal function may improve survival, and bortezomib‐based regimens may be the preferred treatment in patients with severe RI.